2019
DOI: 10.1080/02705060.2018.1529637
|View full text |Cite
|
Sign up to set email alerts
|

Age-0 walleye Sander vitreus display length-dependent diet shift to piscivory

Abstract: The ontogenetic diet shift to piscivory can be energetically beneficial for fish growth and allows larger, more energetically profitable prey to be consumed. A shift to piscivory may be easier for longer individuals within a cohort due to larger gape size, and an early shift is likely advantageous, potentially leading to increased growth rates and survival. Such length-dependent ontogenetic diet shifts may explain the intracohort variability in length that is common for age-0 walleye (Sander vitreus). The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Age-0 white bass size appears to influence food habits as the occurrence of higher trophic level prey items (especially age-0 gizzard shad) were observed at !80 mm TL. Age-0 walleye within the study reservoir have been observed to display a similar ontogenetic diet shift from consuming Calanoida to age-0 gizzard shad at 47 and 77 mm (Uphoff et al 2019). However, in contrast to age-0 white bass, Uphoff et al (2019) found the entire cohort of age-0 walleye eventually shifted to piscivory and thereafter largely consumed gizzard shad.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Age-0 white bass size appears to influence food habits as the occurrence of higher trophic level prey items (especially age-0 gizzard shad) were observed at !80 mm TL. Age-0 walleye within the study reservoir have been observed to display a similar ontogenetic diet shift from consuming Calanoida to age-0 gizzard shad at 47 and 77 mm (Uphoff et al 2019). However, in contrast to age-0 white bass, Uphoff et al (2019) found the entire cohort of age-0 walleye eventually shifted to piscivory and thereafter largely consumed gizzard shad.…”
Section: Discussionmentioning
confidence: 78%
“…Age-0 walleye within the study reservoir have been observed to display a similar ontogenetic diet shift from consuming Calanoida to age-0 gizzard shad at 47 and 77 mm (Uphoff et al 2019). However, in contrast to age-0 white bass, Uphoff et al (2019) found the entire cohort of age-0 walleye eventually shifted to piscivory and thereafter largely consumed gizzard shad. Age-0 gizzard shad availability is fairly consistent and not suspected to be limiting in this reservoir (Miller et al 2018b), suggesting gizzard shad would be available for age-0 white bass to consume.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Walleye is a popular sportfish throughout North America and is often stocked to supplement and maintain populations (Barton, 2011; Ellison & Franzin, 1992; Fenton et al, 1996). Walleye undergo ontogenetic shifts during their first year critical for growth and survival (Einfalt & Wahl, 1997; Mathais & Li, 1982; Pelham et al, 2001; Quist et al, 2002; Raisanen & Applegate, 1983; Uphoff et al, 2019). Walleye begin feeding on zooplankton after endogenous feeding at about 8 mm total length (TL) before switching to macroinvertebrates (35–50 mm TL) and eventually to fish (60–80 mm TL; Galarowicz & Wahl, 2005; Mathias & Li, 1982; Priegel, 1969; Uphoff et al, 2019).…”
Section: Introductionmentioning
confidence: 99%